Mantel, Hilary. Bring Up the Bodies. London: Fourth Estate, 2012. 414 pp. - Albert, Noémi (FOCUS: Papers in English Literary and Cultural Studies, 2014)
Bring Up the Bodies is the second volume of a planned trilogy, the first one being Wolf Hall, published in 2009. Both are historical novels treating the period of the reign of Henry VIII, depicting the notorious king and his court. Hilary Mantel’s talent for writing historical fiction earned her the title of the first woman writer to receive the Booker Prize twice, for the two above-mentioned novels. The reader of these novels enters the world of the kings and queens of England, and becomes acquainted with their most secret thoughts and problems, as well as with their follies and hidden dreams.